Long-Run Effects of Childhood Shocks on Health in Late Adulthood: Evidence from the Survey of Health, Ageing, and Retirement in Europe - Nicole Halmdienst; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2013)
In this paper we address the long-run effects of childhood shocks on health in late adulthood. Applying a life-course approach and data from SHARE we estimate direct and indirect effects of shocks like relocation, dispossession, or hunger on health outcomes after age fifty. Having lived in a childrens home, in a foster family, or having suffered a period of hunger turn out to be the most detrimental. Using a finite mixture model, which allows to classify the associations between shocks and later health into a-priori unknown groups, we show that some adverse shocks have opposite effects for specific groups.
Keywords: J1; I12; J13; 330; Early life experience; health; Europe